Vortex cooled air turning of induction-hardened raceway on the wind turbine-bearing ring - Bošnjaković, Mladen; Maglić, Olivera; Moškun, Dragomir; Crnac, Zoran (2019)
In the turning process of hard materials with CBN cutting inserts, metalworking fluid is not advisable as it results in poorer quality of finished surface and shortening of the tool life. Dry machining, otherwise, develops excessive heat, residual stresses in the workpiece material due to thermal stress, and therefore causes possible problems of achieving tolerances on larger workpieces. During the dry turning of induction hardened raceway on the wind turbine-bearing ring of 1500 mm in diameter, problems with achieving tolerances occurred. The vortex-cooled air implementation during turning resulted in achieving designing tolerances of the workpiece, with better surface roughness and with less tool wear. The result was 50% lower cost of cutting inserts and small operating costs associated with air consumption. The vortex-cooled air implementation makes it possible to extend the tool life of CBN cutting inserts and thus higher cost-effectiveness of machining.
Bibliografija: 13 jed.
Abstract.
Keywords: Vjetroturbine -- Vrtložno hlađenje zraka -- Naprezanje materijala